Insight into supported single-atom catalysts design for thermocatalytic, electrocatalytic and photocatalytic conversion CO2 to CH4 - Aziz F.F.A.; Timmiati S.N.; Samidin S.; Fauzi A.A.; Wan Isahak W.N.R.; Chitraningrum N.; Jalil A.A.; Zainul Abidin A.F.; Salehmin M.N.I. (Korean Society of Industrial Engineering Chemistry, 2025)
One of the greenest techniques to mitigate the current issues of global climate and energy crisis is to transform CO2 into value-added chemicals. Recently, catalysts composed of supported isolated metal atoms were fabricated for CO2 conversion to methane. Herein, to offer direction for the logical design of efficient catalysts, this review focused on the development of these catalysts in thermo-, photo- and electro-catalytic reactions of CO2 methanation. In addition, the theoretical study on the structure of single atoms anchored to the supported materials and the mechanism of the designed catalysts towards active species were reviewed to construct effective catalysts for CO2 methanation. The challenges and future prospects on the merits of combining isolated-atom catalysts with their support materials were also addressed. This review not only highlighted the single-atom-based catalyst development but also offered strategies for designing particular catalysts to be utilized in actual industrial applications in CO2 to methane. ? 2024 The Korean Society of Industrial and Engineering Chemistry